The Effectiveness of Problem-Based Learning in Enhancing Student Achievement in Islamic Religious Education - Abdul Roni (Jurnal Keprofesian Guru Keagamaan, 2025)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model in increasing students' interest and learning outcomes in Asmaul Husna material in Islamic Religious Education. The urgency of this study lies in the importance of fostering a deep understanding of divine values through an active and meaningful learning approach. The research used the Classroom Action Research (CAR) method, which involved four stages of planning, implementation, observation, and reflection with 18 participants from grade V of SD Negeri 004 Ceruk, Natuna Regency. Data were collected through questionnaires, observations, and learning outcome tests. The analysis showed an increase in learning interest from moderate to high, as well as an increase in learning achievement from 72% in cycle I to 94% in cycle II. These findings confirm that the application of the PBL model is not only effective in increasing student interest and learning outcomes but also contributes to strengthening spiritual values and understanding the meaning of Asmaul Husna in the context of Islamic education.